Conjugated Polymer Dots for Ultra‐Stable Full‐Color Fluorescence Patterning. Issue 21 (22nd July 2014) - Chang, Kaiwen; Liu, Zhihe; Chen, Haobin; Sheng, Lan; Zhang, Sean Xiao‐An; Chiu, Daniel T.; Yin, Shengyan; Wu, Changfeng; Qin, Weiping
<x xml:space="preserve">Abstract</x> Stable full‐color fluorescence patterning are achieved by multicolor polymer‐dot inks. The fluorescent patterns show extraordinary stability upon various treatments, offering a superior combination of bright fluorescence, excellent photostability, chemical resistance, and eco‐friendship. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>